Industri 4.0 dan Pendidikan (Upaya Perguruan Tinggi dalam Mempersiapkan Kelulusan yang Siap Terhadap Gencaran Serangan Revolusi Industri 4.0) - Nia Yunia Sari (Tarbawi: Journal of Islamic Education, 2021)
The society will always continue to change along with the times. And changes that occur in these communities are natural and unavoidable, although that the changes between one community and another will be different. Likewise with the modernization process. The modernization in certain societies will be different from other societies both in the process and in acceptance depending on the needs and desires of the community itself. Changes that occur in these societies are modernization process that will handcuff the community to consumerist culture, hedonism and others. Modernization is a form of society social change from a traditional society to a developed society following the development of other society which are considered to be more advanced and developing first. Era 4.0 is where the current development are running so fast and rapid. Era 4.0 brought much of changes with all its effect. The world community is always changing so fast. The change was dramatic at exponential speed. Changes that are very influential in several sektors of human life. And nothing can be separated from this change. The entry of the 4.0 era in people’s lives is colored with artificial intelligence, the era of super computers, genetic engineering, nanothecnology, innovation, etc. where sophisticated technology such as the internet of things, wearables, robotic and 3D printing enters all sektors of the industri and involves various stakeholders ranging from institution, governments, industri association, businesses, technology providers, research institutions and also education. The world of education is also inseparable from the grip of the 4.0 era modernization. Now a days, education runs fast in catching up with the times, following modernization. However, with this relity the community must be smart in choosing which of the modernization processes will be able to change society for the better, so that the benefits of modernization can be felt positively.